Acute application of a transdermal nitroglycerin patch protects against prolonged forearm ischemia‐induced microvascular dysfunction. (19th December 2019) - Soares, Rogerio N.; Proctor, David N.; de Oliveira, Gustavo V.; Alvares, Thiago Silveira; Murias, Juan M.
Abstract: Introduction: Prolonged limb blood flow occlusion (ie, tourniquet application during limb surgery) causes transient microvascular dysfunction. We examined the ability of a local nitric oxide donor (transdermal nitroglycerin) administered during prolonged cuff forearm occlusion to protect against microvascular dysfunction and to alter brachial artery dilation. Methods: Ten healthy men (28 ± 8 years) participated in the study. During the control visit, they completed three vascular occlusion tests in the right arm termed, PRE (5‐min occlusion), POSTimmediate (20‐min occlusion), and POST30min (5‐min occlusion). During the nitroglycerin visit, subjects completed the same vascular occlusion tests, but with a nitroglycerin patch placed over the contralateral forearm during the 20‐min occlusion test. Micro‐ and macrovascular function were assessed using the near‐infrared spectroscopy‐derived reperfusion upslope (reperfusion slope, %.s −1 ) and flow‐mediated dilation (%FMD), respectively. Results: The reperfusion slope (1.44 ± 0.72%.s ‐1 ) and the %FMD (15.0 ± 2.8%) of the POSTimmediate test of the nitroglycerin condition were significantly ( P < .05) higher than the reperfusion slope (1.01 ± 0.37%.s −1 ) and %FMD (6.77 ± 1.8%) during the POSTimmediate test of the control visit. Conclusion: Transdermal nitroglycerin protects against ischemia‐induced microvascular dysfunction and causes marked dilation of the brachial artery %FMD.